Razmatranje emocija i senzacija u neuronaučnom kontekstu - Greš, Alen; Staver, Dijana; Radovančević, Ljubomir (Scripta Medica, 2024)
Understanding emotions and sensations from a neuroscientific context is essential for unravelling the complex mechanisms underlying human behaviour and cognition. Emotions are created by maintaining a positive or negative relationship of an individual towards the experiences and facts of reality. Sensations are the result of the influence of the material world on our senses or receptors. Recent advancements in neuroimaging techniques, such as functional magnetic resonance imaging (fMRI) and electroencephalography (EEG) have provided unprecedented insights into the neural circuitry underlying emotions and sensations. Additionally the role of neurotransmitters, neural networks and brain regions are implicated in emotion regulation, sensory processing and their integration. Furthermore, there is impact of emotional and sensory dysregulation on various psychiatric disorders, including anxiety, depression and post-traumatic stress disorder (PTSD), highlighting potential avenues for therapeutic interventions. Overall, the importance of interdisciplinary research is in bridging the gap between neuroscience and psychology, paving the way for a deeper understanding of human emotions and sensations which is reflected in both simple experiences is emphasised.